UNUSUAL ABUNDANCE OF PSEUDOSCIAENA DIACANTHVS (LACEPEDE) OFF GOA - Dhawan, M Rajinder (Indian Journal of Fisheries, 2011)
In November 1964 and September-October 1965, the purse-seiner of the Directorateof Fisheries, Panaji (Gof), landed unusually large catches of Pseudosciaena diacanthus.The catches were dominated by fish weighing 12 to 14 kg and ranged in size 75-120 cm.The data indicate the possibility of finding new fishing ground for 'ghol' in the deeper regionalong the Goa coast.